Pengaruh Promosi Zakat Melalui Media Sosial Terhadap Minat Berzakat (Pada Rumah Zakat Kota Medan) - Syahridho, Afif Alwan; Br. Pinem, Rasta Kurniawati (Universitas Muhammadiyah Sumatera Utara, 2023)
A research problem of this study is whether there is an influence of Rumah Zakat social media on people's interest in zakat at Rumah Zakat Kota Medan, This study aims to find outthe Effect of Zakat Promotion through Social Media on Interest in Zakat House in Medan City. There is a positive influence on people's interest in becoming muzakki and social media is an institutional tool for delivering information, so that people are easier to manage information obtained from Rumah Zakat, and the more information obtained, the more interest the community has to become muzakki at Rumah Zakat Kota Medan.This research uses a descriptive method with a quantitative approach. The samples in this study were Rumah Zakat and Muzakki staff. This quantitative research uses the distribution of questionnaires to respondents as many as 92 people by collecting data using research instruments, statistical data analysis and describing variables as they are supported by data in the form of numbers generated from actual circumstances.The results showed that there was a positive and significant influence between the promotion of zakat through social media on the interest in zakat at the house of zakat in Medan City. This shows that public interest in giving zakat at Rumah Zakat Kota Medan has increased after promoting through social media